Jews, Muslims and the Ritual Male Circumcision Debate: Religious Diversity and Social Inclusion in Germany - Yurdakul, Gökçe (2016)
On 7 May 2012, the Cologne regional court ruled that circumcising young boys was a form of previous bodily harm (körperverletzung). Although both Muslims and Jews circumcise infant boys as a religious practice, the Cologne court found that the child’s “fundamental right to bodily integrity” was more important than the parents’ rights, leaving Muslim and Jewish parents under suspicion of causing bodily harm to their children. After heated public discussions and an expedited legal process, legal authorities permitted the ritual circumcision of male children under a new law. However, the German debates on religious diversity are not yet over. On the third anniversary of the Court decision in 2015, thirty-five civil society organisations organised a rally in Cologne for “genital autonomy”, calling for a ban on ritual male circumcision. In this article, I will focus on religious diversity, which is undergoing changes through minority and immigrant claims for religious accommodation. Analysing the ongoing controversies of ritual male circumcision in Germany, I argue that this change is best observed with Muslim and Jewish claims for practicing their religion. By using political debates, news reports and information provided by lawyers and medical doctors who were involved in the public debate, I show that religious diversity debates are a litmus test for social inclusion: Muslims and Jews, in this context, are both passive subjects of social inclusion policies and active participants in creating a religiously diverse society in Germany.